The extent of imagery in New Zealand company annual reports : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Accountancy at Massey University - Simpson, Linda Louise (Massey University, 1998)
Imagery, and in particular photography, has become a regular and sometimes spectacular feature of company annual reports. From a broad perspective, photography can be seen to have a multiplicity of functions in society including the presentation of a factual, documentary view of the world, providing an interpretative art form, being used as advertising, and even being seen as pure entertainment. Photography can be seen to reflect the nature of society, while simultaneously altering and constructing society values. As the New Zealand Government continues to advocate free-market policies, resulting in more and more decisions about the nature of New Zealand society being put into corporate hands, concerns are being voiced regarding the degree to which New Zealand citizens have a democratic vote on how their society is constructed. These concerns relate specifically to the nature of corporate values, and how they impact on New Zealand society. A logical place for a statement of corporate values to be found is the company annual report. This study explores and investigates the use of imagery in company annual reports by using the imperatives contained in the political economy of accounting: be normative, be descriptive and be critical. Two questions are specifically addressed. Firstly, an empirical investigation is made of the extent to which imagery has been present in some New Zealand company annual reports for the period 1970 - 1997. Secondly, these annual reports are examined to determine whether, from the perspective of the researcher, company values that inspire and underlie company activities are reported by the use of imagery. In this way, imagery in annual reports may highlight a direct link between company values and social values in general. This study is important in that if companies use imagery, and in particular photography, to report their company values it may contribute to further understanding of the constitutive nature of the company annual report from a broad societal perspective, rather than from that reflected only in the accounting and financial numbers. This also has consequences for the nature of the corporate social report, an area growing in importance in the accounting field. This study may also reveal previously unknown features regarding the role accounting plays when it attempts to represent some aspect of a company's activities. Key Words: Annual Reports, Imagery, Corporate Social Report.
Keywords: New Zealand; Corporation reports; Corporate image